Determining the Role of Fe‐Doping on Promoting the Thermochemical Energy Storage Performance of (Mn1−xFex)3O4 Spinels. Issue 10 (9th September 2021) - Carrillo, Alfonso J.; Chinchilla, Lidia E.; Iglesias‐Juez, Ana; Gutiérrez‐Rubio, Santiago; Sastre, Daniel; Pizarro, Patricia; Hungría, Ana B.; Coronado, Juan M.
Abstract: Mn oxides are promising materials for thermochemical heat store, but slow reoxidation of Mn3 O4 to Mn2 O3 limits efficiency. In contrast, (Mn1− x Fe x )3 O4 oxides show an enhanced transformation rate, but fundamental understanding of the role played by Fe cations is lacking. Here, nanoscale characterization of Fe‐doped Mn oxides is performed to elucidate how Fe incorporation influences solid‐state transformations. X‐ray diffraction reveals the presence of two distinct spinel phases, cubic jacobsite and tetragonal hausmannite for samples with more than 10% of Fe. Chemical mapping exposes wide variation of Fe content between grains, but an even distribution within crystallites. Due to the similarities of spinels structures, high‐resolution scanning transmission electron microscopy cannot discriminate unambiguously between them, but Fe‐enriched crystallites likely correspond to jacobsite. In situ X‐ray absorption spectroscopy confirms that increasing Fe content up to 20% boosts the reoxidation rate, leading to the transformation of Mn 2+ in the spinel phase to Mn 3+ in bixbyite. Extended X‐ray absorption fine structure shows that FeO length is larger than MnO, but both electron energy loss spectroscopy and X‐ray absorption near edge structure indicate that iron is always present as Fe 3+ in octahedral sites. These structural modifications may facilitate ionic diffusion during bixbyite formation. Abstract : (Mn1− x Fe x )3 O4 is a promising material for thermochemical heat storage because Fe‐doping accelerates the reoxidation to (Mn1− x Fe x )2 O3 easing continuous cycling. Here, the specific effect of Fe is studied on the nanoscale with high‐resolution scanning transmission electron microscopy whereas solid‐state transformations are monitored by in situ X‐ray absorption spectroscopy. These techniques reveal subtle structural changes that may promote ionic diffusion.